2003
DOI: 10.1093/nar/gkg182
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of human centromeres by transformation-associated recombination in yeast and generation of functional human artificial chromosomes

Abstract: Human centromeres remain poorly characterized regions of the human genome despite their importance for the maintenance of chromosomes. In part this is due to the difficulty of cloning of highly repetitive DNA fragments and distinguishing chromosome-specific clones in a genomic library. In this work we report the highly selective isolation of human centromeric DNA using transformation-associated recombination (TAR) cloning. A TAR vector with alphoid DNA monomers as targeting sequences was used to isolate large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 43 publications
3
48
0
1
Order By: Relevance
“…5 Specific alpha satellite DNA arrays from various human chromosomes, such as chromosomes 14,17,21,22, X (and Y inefficiently), have been transferred as purified DNA in order to form centromeres on de novo HACS. [5][6][7][8][9][10][11][12][13] The centromeres formed on the transferred DNA acquire chromatin proteins specific for functional centromeres such as CENP-A a histone H3 variant, only found within active centromere chromatin. 13 Moreover, complete genes can be incorporated into HACs and expressed, as shown for human HPRT (42 kb), 14,15 or GCH1 genes (61 kb).…”
Section: Introductionmentioning
confidence: 99%
“…5 Specific alpha satellite DNA arrays from various human chromosomes, such as chromosomes 14,17,21,22, X (and Y inefficiently), have been transferred as purified DNA in order to form centromeres on de novo HACS. [5][6][7][8][9][10][11][12][13] The centromeres formed on the transferred DNA acquire chromatin proteins specific for functional centromeres such as CENP-A a histone H3 variant, only found within active centromere chromatin. 13 Moreover, complete genes can be incorporated into HACs and expressed, as shown for human HPRT (42 kb), 14,15 or GCH1 genes (61 kb).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from a number of groups have shown that alpha satellite DNA from several human chromosomes is capable of forming de novo centromeres in artificial chromosome assays (11,14,16,18,22,24,34,40,45). Some types of alpha satellite assemble artificial chromosomes that are maintained stably in culture over many cell divisions and contain centromeres that colocalize with kinetochore proteins associated specifically with active centromeres.…”
mentioning
confidence: 99%
“…Southern blot hybridization was performed as described by Kouprina et al (1998) with 32 P-labelled probes. Fluorescence in situ hybridization was performed as described elsewhere (Kouprina et al, 2003). Sequencing.…”
Section: Methodsmentioning
confidence: 99%